Kepuasan Pelanggan: Determinan dan Dampaknya terhadap Loyalitas : Studi Kasus Pelanggan E-Commerce Shopee di Bekasi - Fikri Wijaya; Sri Rakhmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
The objective of this study is to examine the influence of promotion and service quality on customer loyalty through customer satisfaction in the context of Shopee e-commerce in Bekasi. The analysis in this research employs a quantitative approach using primary data. The testing stages include: evaluation of the measurement model (outer model), which covers convergent validity, discriminant validity, and reliability tests; and evaluation of the structural model (inner model), which encompasses R-Square and Q-Square tests, goodness-of-fit assessment, and hypothesis testing involving both direct and indirect effects. Data were collected through questionnaires, resulting in 160 valid respondents. The sampling method used is non-probability sampling with a purposive sampling approach. The analytical tool applied in this study is Smart-PLS version 4.1.1.2. The findings reveal that promotion and service quality significantly affect customer satisfaction in Shopee e-commerce in Bekasi. Furthermore, promotion, service quality, and customer satisfaction collectively influence customer loyalty. Additionally, promotion and service quality contribute to customer loyalty through the mediating role of customer satisfaction.